EXTRACELLULAR VESICLES FROM BLOOD PLASMA STUDIED BY LOW VOLTAGE SCANNING ELECTRON MICROSCOPY - Kondratov, K A; Petrova, T A; Mikhailovskii, V Yu; Ivanova, A N; Kostareva, A A; Fedorov, A V (T͡S︡itologii͡a, 2017)
Extracellular vesicles are subspherical membranous structures secreted by cells and enriched with different types of biological molecules. The number and the molecular content of these structures depend on pathological conditions and the physiological state of the organism. Extracellular vesicles play an important role in intercellular communication and represent potential disease biomarkers. However, mechanisms of formation, functions and morphological characteristics of extracellular vesicles are still studied insufficiently. Low voltage scanning electron microscopy is a promising method to investigate extracellular vesicles, since it does not require conductive coating and therefore enables a high-resolution visualization of morphological details of nanosized objects. This paper presents the results of low voltage scanning electron microscopy study of morphology and size of objects from blood plasma fractions.